A revision of Angolan species in the genus Pedioplanis Fitzinger (Squamata: Lacertidae), with the description of a new species - Parrinha, Diogo; Marques, Mariana P.; Heinicke, Matthew P.; Khalid, Farkhanda; Parker, Kelly L.; Tolley, Krystal A.; Childers, Jackie L.; Conradie, Werner; Bauer, Aaron M.; Ceríaco, Luis M. P. (Zootaxa, 2021)
The genus Pedioplanis reaches its northernmost limit in western Angola, where it is represented by three species, Pedioplanis benguelensis, P. haackei and P. huntleyi. The taxonomic status of P. benguelensis remains problematic, mainly due to the vague original description and the loss of the original type material. Here we provide a revision of the Angolan representatives of the genus, with the description of a new species, Pedioplanis serodioi sp. nov., from the lowlands of southwestern Angola. Phylogenetic analyses using a combination of mitochondrial (16S and ND2) and nuclear (RAG-1) markers, as well as morphological data, support the recognition of the new species. For purposes of nomenclatural stability, we designate a neotype for P. benguelensis and provide motivation to correct the spelling of the specific epithet to “benguelensis”. The clarification of the status of P. benguelensis and the description of a new species contribute to a better understanding of the taxonomy and biogeography of the genus Pedioplanis, as well as the general biogeographic context of southwestern Angola, adding to the growing evidence in favor of the recognition of this region as a hotspot of lizard diversity and endemism. An updated key to the genus is also provided.